A Bobcat Burial and Other Reported Intentional Animal Burials from Illinois Hopewell Mounds. Issue 3 (September 2015) - Perri, Angela R.; Martin, Terrance J.; Farnsworth, Kenneth B.
<x content-type="archive" xml:space="preserve">Abstract</x> The Elizabeth site is a bluff-top mortuary mound group constructed and primarily used during Hopewellian (Middle Woodland) times. Recent reanalysis of nonhuman skeletal remains from the site reveals that an intentional burial previously identified as a dog (Canis familiaris) is actually an immature bobcat (Lynx rufus). As a result of this discovery, we reevaluated eight other purported animal burials from Illinois Middle Woodland mounds, including seven dogs and a roseate spoonbill (Platalea ajaja). The dogs all appear to be intrusive or unrelated burial events, but both the bobcat and the roseate spoonbill were definite Hopewellian mortuary interments. The roseate spoonbill was decapitated and placed beside a double human burial. But the bobcat was a separate, human-like interment wearing a necklace of shell beads and effigy bear canine teeth (Figures 1 and 2). To our knowledge, this is the only decorated wild cat burial in the archaeological record. It provides compelling evidence for a complex relationship between felids and humans in the prehistoric Americas, including possible taming.